Significant role of estrogen in maintaining cardiac mitochondrial functions. Issue 147 (March 2015) - Rattanasopa, Chutima; Phungphong, Sukanya; Wattanapermpool, Jonggonnee; Bupha-Intr, Tepmanas
Highlights: Estrogen and progesterone can reduce cardiac mitochondrial swelling. Estrogen, but not progesterone, modulates mitochondrial ATP synthesis in the heart. Estrogen and progesterone decrease stress-induced mitochondrial ROS production. Abstract: Increased susceptibility to stress-induced myocardial damage is a significant concern in addition to decreased cardiac performance in postmenopausal females. To determine the potential mechanisms underlying myocardial vulnerability after deprivation of female sex hormones, cardiac mitochondrial function is determined in 10-week ovariectomized rats (OVX). Significant mitochondrial swelling in the heart of OVX rats is observed. This structural alteration can be prevented with either estrogen or progesterone supplementation. Using an isolated mitochondrial preparation, a decrease in ATP synthesis by complex I activation in an OVX rat is completely restored by estrogen, but not progesterone. At basal activation, reactive oxygen species (ROS) production from the mitochondria is not affected by the ovariectomy. However, after incubated in the presence of either high Ca 2+ or antimycin-A, there is a significantly higher mitochondrial ROS production in the OVX sample compared to the control. This increased stress-induced ROS production is not observed in the preparation isolated from the hearts of OVX rats with estrogen or progesterone supplementation. However, deprivation of female sex hormones has no effect on the protein expression of electron transport chain complexes, mitofusin 2, or superoxide dismutase 2. Taken together, these findings suggest that female sex hormones, estrogen and progesterone, play significant regulatory roles in maintaining normal mitochondrial properties by stabilizing the structural assembly of mitochondria as well as attenuating mitochondrial ROS production. Estrogen, but not progesterone, also plays an important role in modulating mitochondrial ATP synthesis.